Ultrasound differential diagnosis of different forms of stomatogenic maxillary sinusitis - S. D. Varzhapetyan (Zaporozhye State Medical University, 2016)
Objective: to improve the efficiency of diagnosis of various forms of stomatogenic maxillary sinusitis. Material and methods. Ultrasonography of the maxillary sinuses in 86 patients (mean age 40,4 ± 3,2 years) with clinical signs of maxillary sinusitis has been conducted with the help of ultrasound diagnostic apparatus ACUSON X 500, ATSmod.539 (SIEMENS, USA) in B-mode, as described by V. Shilenkova. Initial evaluation of patients allowed to diagnose iatrogenic form of stomatogenic sinusitis in 68 (79.1%) patients, odontogenic form - in 18 (20.9%). Assessment of pathological changes has been performed in the sinuses by values given in the literature [2, 3, 6, 7]. Results of the study are presented in the tables in absolute values (abs.), as fractions (percent) and the error of share. Statistical analysis of the absolute values has been determined by Student's method, comparison of share - by xi-square method. Results of the study. Sonographic picture of the maxillary sinus reflects the clinical and radiological features of the studied forms of the disease. Ultrasonic status indicators of mucosa of the maxillary both in odontogenic (44.4%) and in iatrogenic (45.6%) sinuses indicated more in the absence of pathological changes in its thickness, which corresponded to isogenic signal. While in iatrogenic form of stomatogenic maxillary sinusitis such sonographic signs dominated: the hyperechogenicity membrane (30.8%), the heterogeneity of its echostrucure (52.9%), hyperechoic nature of the contents of the sinus (39.7%), sinus arcuate contour of the rear wall (36.8 %). While in odontogenic maxillary sinusitis of stomatogenic form, such signs dominated: hypoechogenicity membrane (27.8%), the homogeneity of its echostructure (45.6%); acoustic shadow in sinus (72.2%), the arcuate contour of the rear wall (27.8%). Conclusions. 1. Reduced forms of stomatogenic maxillary sinusitis in the ultrasonographic picture the intact sinus mucosa (in 44.4 and 45.6% of cases) and serous exudate character is identified in the majority of patients (36.8 and 27.8%). 2. Ultrasound signs of chronic inflammation in the sinus with the presence of a plurality of inflammatory origin inclusions, mucosal sclerosis and serous effusion are more typical for iatrogenic form of stomatogenic maxillary sinus. 3. Ultrasound signs of acute catarrh with exudation in the prevalence of mucosal thickness, lack of content in the lumen of the sinuses, serous effusion are more typical for forms of odontogenic form of stomatogenic maxillary sinus.